Miscarriage: Related factors and management among the women with miscarriage admitted to the gynaecological wards of Teaching Hospital Jaffna - Paviththiran, S.; Majuran, S.; Shanuga, A.; Chandrasekara, S.A.M.B.; Aasaththusana, M.I.F.; Coonghe, P.A.D.; Guruparan, K. (University of Jaffna, 2024)
Introduction and objective: The term miscarriage is used to describe a pregnancy that fails to progress beyond the 24th week, leading to death or foetal expulsion. Accounting for about a quarter of all pregnancies, miscarriage is known to be associated with uterine abnormalities, genetics, age, medical conditions, medications, and lifestyle changes. This study invesstigated the association of sociodemographic, obstetric factors, medical conditions and management of women with miscarriages admitted to the gynaecological wards of Teaching Hospital Jaffna. Methods: This was a hospital-based descriptive cross-sectional study among 100 mothers admitted to the gynecological wards of Teaching Hospital Jaffna. Data were collected using an interviewer-administered questionnaire and data extraction sheet and analyzed with SPSS software. The independent t-test was used to test for associations. Results: Our study found that 69% of mothers were between 20-34 years, with a mean maternal age of 31.3 years and a mean BMI of 23.8 kgm-2 . Among them, 75% were unemployed, 21% were degree holders and 83% were from low-income families. Almost all were married and 59% lived in a nuclear family. Over three-fourths (76%) of mothers had not taken folic acid in the 3 months prior to conception. The majority had first- trimester miscarriages (69%) with 74% experiencing vaginal bleeding. Hypothyroidism (12%) was the most common medical condition encountered. In the sample, 17%, 66% and 17% were managed conservatively, medically and surgically, respectively. Misoprostol was the mainline drug used for medical management. A significant association was found between prescription of antibiotics and POA at miscarriage (p=0.037). Conclusion and recommendations: The majority of women with miscarriage were admitted with a first-trimester miscarriage. Most had not taken pre-conceptional folic acid supplementation which is a known risk factor. The majority were medically managed with misoprostol. Promoting pre-conceptional folic acid intake and conducting population-based studies to assess risk factors in local settings is recommended.
Keywords: Miscarriage; Pre-conceptional folic acid; Misoprostol; Hypothyroidism; Jaffna